2015
DOI: 10.1007/s11307-015-0857-1
|View full text |Cite
|
Sign up to set email alerts
|

124I-PET Assessment of Human Sodium Iodide Symporter Reporter Gene Activity for Highly Sensitive In Vivo Monitoring of Teratoma Formation in Mice

Abstract: This is the first study to generate stably hNIS-expressing murine PSCs. Since the differentiation potential was preserved, hNIS-expressing cells are suitable for PSC-based forward programming approaches. Teratoma formation from undifferentiated cells can be monitored in vivo by PET with high specificity on a quantitative level. Due to its anticipated lack of immunogenicity in humans, hNIS is a promising reporter gene for clinical translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…However, they introduce the risk of forming teratomas. To study this phenomenon, Lehner and colleagues (153) generated murine PSCs stably expressing human NIS (hNIS) and injected them into mice to induce teratoma formation. By 124 I − PET, they monitored the growth of the teratomas and reported a correlation between tumor mass and tracer uptake.…”
Section: Nis As a Valuable Molecule To Monitor The Fate Of Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they introduce the risk of forming teratomas. To study this phenomenon, Lehner and colleagues (153) generated murine PSCs stably expressing human NIS (hNIS) and injected them into mice to induce teratoma formation. By 124 I − PET, they monitored the growth of the teratomas and reported a correlation between tumor mass and tracer uptake.…”
Section: Nis As a Valuable Molecule To Monitor The Fate Of Stem Cellsmentioning
confidence: 99%
“…By 124 I − PET, they monitored the growth of the teratomas and reported a correlation between tumor mass and tracer uptake. They observed that hNIS expression and 124 I − did not affect the viability or the differentiation of PSCs and concluded that NIS-mediated 124 I − uptake can be used to monitor the formation of potential teratomas when PSCs are injected (153). …”
Section: Nis As a Valuable Molecule To Monitor The Fate Of Stem Cellsmentioning
confidence: 99%
“…hNIS is a relatively well-established radionuclide reporter gene that has been shown to track cells both in rodents 20 , 27 and in larger animals 15 , 17 . The feasibility to use hNIS for monitoring murine teratoma formation, after stable murine ESC transfection, has also been demonstrated by Lehner et al 28 . In contrast, hSSTr2 has not been frequently used for cell tracking.…”
Section: Discussionmentioning
confidence: 91%
“…[16][17][18] Due to these desirable attributes, NIS has been used in many applications, such as tracking viral infection, replication, and spread in oncolytic virotherapy in animals and humans, tracking the intensity and durability of gene and cell therapies, and for treatment of NIS-expressing tumors with radioisotopes. 14,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Despite the growing utility of NIS as a reporter gene, there remain several challenges to NIS imaging and therapy. Endogenous NIS expression, efflux of radiotracer from NIS-expressing cells, and suboptimal NIS expression in target tissues decrease the efficacy of NIS imaging.…”
Section: Introductionmentioning
confidence: 99%